ARTISTIC DECORATION OF FAIENCE WARES IN LATVIA IN THE SECOND HALF OF THE 19TH CENTURY AND THE BEGINNING OF THE 20TH CENTURY - Brants, Inese (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2018)
This research paper is an investigation of the techniques used in decoration of Riga faience from the beginning of faience production in Riga in the middle of the 19th century until the First World War. Relatively few products from this period are represented in the Riga History Museum and Riga Porcelain Museum; in the summer of 2016, the author visited 22 regional history and art museums of Latvia and got acquainted with their ceramics collections in order to find more historical artefacts and gain more complete overview of porcelain decoration techniques used for them. Work with museum collections revealed a lot of previously unknown information about the development of decoration techniques during the faience production period in Riga, from 1841 to 1962. The article deals with the problems of faience terminology and development of decoration techniques in the period from 1841 until the First World War. The article offers conclusions on the nature of the collections of Latvian regional museums, their collection–building strategy, preservation conditions, state of the objects and their availability for exploratory work.